2010
DOI: 10.1186/1477-7827-8-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adiponectin on bovine granulosa cell steroidogenesis, oocyte maturation and embryo development

Abstract: BackgroundAdiponectin is an adipokine, mainly produced by adipose tissue. It regulates several reproductive processes. The protein expression of the adiponectin system (adiponectin, its receptors, AdipoR1 and AdipoR2 and the APPL1 adaptor) in bovine ovary and its role on ovarian cells and embryo, remain however to be determined.MethodsHere, we identified the adiponectin system in bovine ovarian cells and embryo using RT-PCR, immunoblotting and immunohistochemistry. Furthermore, we investigated in vitro the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 52 publications
5
115
2
8
Order By: Relevance
“…Indeed, the expression of adiponectin, AdipoR1 and AdipoR2 was higher in the theca and cumulus cells and the oocytes of dominant follicles compared with those of atretic follicles during both the follicular and luteal phases (Tabandeh et al, 2012). In our laboratory, we have shown that adiponectin decreased insulin-induced steroidogenesis and increased IGF-I-induced proliferation of the bovine granulosa cells in culture possibly by a mechanism that involved the ERK1/2 MAPK pathway (Maillard et al, 2010). Lagaly et al (2008), have also observed an inhibitory effect of adiponectin on bovine steroidogenesis but only in the theca cells.…”
Section: Metabolic Hormonesmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, the expression of adiponectin, AdipoR1 and AdipoR2 was higher in the theca and cumulus cells and the oocytes of dominant follicles compared with those of atretic follicles during both the follicular and luteal phases (Tabandeh et al, 2012). In our laboratory, we have shown that adiponectin decreased insulin-induced steroidogenesis and increased IGF-I-induced proliferation of the bovine granulosa cells in culture possibly by a mechanism that involved the ERK1/2 MAPK pathway (Maillard et al, 2010). Lagaly et al (2008), have also observed an inhibitory effect of adiponectin on bovine steroidogenesis but only in the theca cells.…”
Section: Metabolic Hormonesmentioning
confidence: 70%
“…In the bovine species, adiponectin and its receptors are present in different follicular cells (oocytes, theca, granulosa and cumulus cells) and luteal cells (Maillard et al, 2010) (Table 1). Moreover, it has been shown that the physiological status of the ovary is related to the pattern of expression of adiponectin and its receptors in follicular and luteal cells from the bovine ovary (Tabandeh et al, 2010).…”
Section: Metabolic Hormonesmentioning
confidence: 99%
“…Adiponectin had an inhibitory effect on in vitro secretion of progesterone by porcine luteal cells on days 10 to 12 of the estrous cycle (Maleszka et al 2014a). The effect of adiponectin on ovarian basal progesterone secretion was also suggested in studies on cows, rats, and humans (Chabrolle et al 2009;Mailard et al 2010;Lagaly et al 2008). Moreover, the insulin-induced production of progesterone and estradiol by bovine granulosa cells was significantly decreased as a result of adiponectin treatment (Mailard et al 2010).…”
Section: Discussionmentioning
confidence: 80%
“…The effect of adiponectin on ovarian basal progesterone secretion was also suggested in studies on cows, rats, and humans (Chabrolle et al 2009;Mailard et al 2010;Lagaly et al 2008). Moreover, the insulin-induced production of progesterone and estradiol by bovine granulosa cells was significantly decreased as a result of adiponectin treatment (Mailard et al 2010). In the study with bovine theca interna cells, Lagaly et al (2008) observed that adiponectin decreased LH and insulin-induced production of progesterone.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation